Reliable Software Technologies - Ada-Europe 2008 13th Ada-Europe International Conference on Reliable Software Technologies, Venice, Italy, June 16-20, 2008. Proceedings - Kordon, Fabrice; Vardanega, Tullio (Programming and Software Engineering,, 2008)
This book constitutes the refereed proceedings of the 13th International Conference on Reliable Software Technologies, Ada-Europe 2008, held in Venice, Italy, in June 2008. The 20 revised full papers presented were carefully reviewed and selected from numerous submissions. The conference proceedings published in this volume cover topics ranging from formal verification to real-time systems via concurrency, embedded systems, language technologies, model-driven engineering and applications of Petri Nets.